Penanaman Nilai Literasi Keuangan pada Anak LKSA Santa Anna Bojonegoro - Eka Putri Rahmawati; Dewi Rochmayanti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Financial literacy is an important skill that needs to be introduced from an early age so that children can understand the value of money and manage it wisely. This activity aims to improve basic financial literacy among children at LKSA Santa Anna Bojonegoro through a participatory educational approach. The implementation method included pre tests, interactive material delivery, discussions, and simple case studies on priority scales and budgeting. Of the 37 participants, 20 children aged 8–18 were sampled. The pre-test results showed an average understanding of basic financial literacy concepts of 73.6%. After the activity, there was an increase in understanding, indicated by the participants' ability to differentiate needs from wants, develop spending plans, and foster savings awareness. The facilitator also found that the main issue among participants was self-control over consumptive behavior, which was addressed through reflective exercises and the implementation of strategies for delaying purchasing decisions. This activity was well-received and proven effective in fostering a rational mindset regarding pocket money management. Overall, this socialization of basic financial literacy can be the first step in developing responsible financial habits from an early age.